UV photocatalytic activity of Au@ZnO core–shell nanostructure with enhanced UV emission1. Issue 80 (2nd September 2015) - Jiang, Tingting; Qin, Xueying; Sun, Ye; Yu, Miao
<x xml:space="preserve">Abstract</x> Au@ZnO core–shell nanostructures with increased ultraviolet photoluminescence emissions present remarkably enhanced ultraviolet photocatalytic properties, based on bidirectional electron transfer between Au and ZnO.